MATHEMATICAL REASONING CHARACTERISTICS ACROSS ABILITY LEVELS IN METACOGNITIVE-BASED DEEP LEARNING - Rivka Larose Lubis; Ramlah Ramlah; Indra Budiman (Universitas Muhammadiyah Metro, 2026)
Mathematical reasoning ability is an essential competency in mathematics learning; however, many students still experience difficulties in constructing arguments, applying concepts, and drawing logical conclusions. Metacognitive-based deep learning is expected to support reasoning development by encouraging students to plan, monitor, and evaluate their thinking processes. This study aimed to describe the characteristics and levels of junior high school students’ mathematical reasoning ability in a metacognitive-based deep learning environment. A descriptive quantitative approach was employed involving 31 seventh-grade students of SMP Yos Sudarso Karawang. Data were collected through a mathematical reasoning test consisting of two essay items based on four indicators: making conjectures, applying mathematical concepts, carrying out logical procedures, and drawing conclusions. The instrument met the criteria of validity, reliability, discrimination index, and difficulty index. The results showed that 6.45% of students were categorized as high, 70.97% as medium, and 22.58% as low. High-level students fulfilled all reasoning indicators, medium-level students showed weaknesses in procedures and conclusions, and low-level students experienced difficulties in concepts, procedures, and conclusions. These findings provide a deeper understanding of students’ mathematical reasoning characteristics across ability levels and may inform more reflective mathematics instruction. Kemampuan penalaran matematis merupakan kompetensi penting dalam pembelajaran matematika, namun masih banyak peserta didik yang mengalami kesulitan dalam menyusun argumen, menerapkan konsep, dan menarik kesimpulan secara logis. Deep learning berbasis metakognitif diharapkan dapat mendukung pengembangan penalaran melalui kegiatan merencanakan, memantau, dan mengevaluasi proses berpikir. Penelitian ini bertujuan untuk mendeskripsikan karakteristik dan level kemampuan penalaran matematis peserta didik SMP dalam pembelajaran deep learning berbasis metakognitif. Penelitian menggunakan pendekatan deskriptif kuantitatif dengan melibatkan 31 peserta didik kelas VII SMP Yos Sudarso Karawang. Data dikumpulkan melalui tes kemampuan penalaran matematis yang terdiri atas dua soal uraian berdasarkan empat indikator. Instrumen telah memenuhi kriteria validitas, reliabilitas, daya pembeda, dan indeks kesukaran. Hasil penelitian menunjukkan bahwa 6,45% peserta didik berada pada level tinggi, 70,97% pada level sedang, dan 22,58% pada level rendah. Peserta didik pada level tinggi memenuhi seluruh indikator penalaran, peserta didik pada level sedang masih menunjukkan kelemahan pada prosedur dan kesimpulan, sedangkan peserta didik pada level rendah mengalami kesulitan dalam konsep, prosedur, dan kesimpulan. Temuan ini memberikan pemahaman yang lebih mendalam mengenai karakteristik penalaran matematis pada setiap level kemampuan dan dapat menjadi pertimbangan dalam pembelajaran matematika yang lebih reflektif.